Collapsing Focal Segmental Glomerulosclerosis in a Patient with Acute Malaria - Najamus Sehar; Emad Gobran; Suzanne Elsayegh (Case Reports in Medicine)
Introduction. Collapsing focal segmental glomerulosclerosis (FSGS) is most commonly seen in association with HIV infection. Rare data is available about the association between collapsing FSGS and malaria. Case Description. A 72-year-old African male patient presented to the hospital for generalized body aches, fatigue, fever, and night sweats for three days. He had history of recent travel to Ghana. Patient looked in acute distress and was shivering. Laboratory tests showed elevated serum creatinine (Cr) of 2.09 mg/dL (baseline was 1.5 mg/dL in 2012). Hospital course was significant for rapid elevation of Cr to 9.5 mg/dL and proteinuria of 7.9 grams. Autoimmune studies resulted negative. Blood smear resulted positive for Plasmodium falciparum and patient was treated with Artemether/Lumefantrine. Patient’s fever and pain improved, but kidney function continued to deteriorate and he became oliguric. On day seven, he was started on Hemodialysis. Tests for different causes of glomerular pathology were also negative. He underwent left kidney biopsy which resulted in findings consistent with severe collapsing glomerulopathy. Discussion. This case illustrates a biopsy proven collapsing FSGS likely secondary to malarial infection requiring renal replacement therapy. Literature review revealed only few case reports that suggested the possible association of malaria with secondary form of FSGS.